PENGARUH PERTUMBUHAN ASSET DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hayatul Fuad; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the effect of asset growth and sales growth on profitability. This study uses a descriptive quantitative approach which is analyzed using statistical-based partial and multiple regression analysis. The population of the study are retail companies listed on the Indonesia Stock Exchange in 2015 – 2019 as many as 8 companies. The results of this study are asset growth has a positive and significant effect on profitability and sales growth has a significant effect on profitability. The analytical technique used is multiple linear regression analysis with F test and t test. Based on the results of the F test, it is known that the significance value is less than 0.05, which is 0.000, this indicates that the independent variables of asset growth and sales growth simultaneously have a significant effect on profitability. Based on the results of the T test, there is a significant effect of the sales growth variable (X2) on profitability (Y), which is 4.183. Where tcount = 4.183 > t table = 1.943 and sig 0.00 Ftable 5.67 and sig o, oo